2018
DOI: 10.1039/c8ra07031h
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of hierarchical film composed of Co(OH)2@Carbon nanotube core/sheath nanocables and its capacitive performance

Abstract: A uniform Co(OH)2 sheath was anchored on the surface of a conductive CNT by a facile strategy, exhibiting comparatively high specific capacitance and outstanding long cycle life stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This revealed that the coordination assembly did not change the basic structure of the original Co(OH) 2 and the metal-phenol coordination compound was amorphous. [39,40]. In the FT-IR spectrum of Co(OH) 2 @TA-Fe, the absorption peaks at 3415, 2922 cm −1 were attributed to aromatic O-H stretching vibration and C-H stretching, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This revealed that the coordination assembly did not change the basic structure of the original Co(OH) 2 and the metal-phenol coordination compound was amorphous. [39,40]. In the FT-IR spectrum of Co(OH) 2 @TA-Fe, the absorption peaks at 3415, 2922 cm −1 were attributed to aromatic O-H stretching vibration and C-H stretching, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…When tannic acid was chelated with Fe 3+ ions on the surface, the XRD pattern showed no change. This revealed that the coordination assembly did not change the basic structure of the original Co(OH) 2 and the metal-phenol coordination compound was amorphous [39,40]…”
mentioning
confidence: 99%
“…EIS is a quasi-steady-state measurement, which is able to test the electrochemical behavior of electrode without exerting great impact on the electrochemical system due to the low-amplitude perturbation signal. [20][21][22] The Nyquist plot for Ti/Al-LC obtained in saturated NaCl solution at 70 C is shown in Figure 2(b). It is observed that Nyquist plot displays one depressed semicircle within the test frequency range (from 100,000 Hz to 0.01 Hz).…”
Section: Corrosion Resistance and Stabilitymentioning
confidence: 99%
“…The most investigated pseudocapacitive nanoparticles have been conductive polymers and metal oxides, particularly the oxides of transition metals like nickel, cobalt, manganese, titanium, vanadium, molybdenum, tungsten and others. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] The strategies used to prepare such composites can be classied as either in situ decoration of the NPs during the synthesis phase of the nanocarbon material, or post-synthesis methods in which the nanocarbon material is processed to allow for the formation of stable composites upon the addition of the NPs. Methodology-wise, the composite synthesis may proceed through diverse routes, such as solution chemistry, [40][41][42][43][44][45][46][47][48][49][50] hydrothermal or solvothermal methods, [51][52][53][54] self-assembly, [55][56][57] microwave-irradiation, [58][59][60] photo-reduction, 61 mechanical routes, 62,63 electrochemical deposition, 64,65 electrospinning or templating with a carbon precursor, 66,67 and others.…”
Section: Introductionmentioning
confidence: 99%